A Quantitative Analysis of Lexical Similarities in Tabarsiâs Tafsir e Majmaulbayan: Synonymy, Antonymy and Homophone - Seyyed Haydar Shirazi; , Fatemeh Hajizadeh (دراسات فی اللغه العربیه و آدابها)
The study of lexical similarities is one of the most important issues in religious text interpretation without which the comprehension of the Holy Quran is almost impossible. This domain of scholarship dates back to the beginning of the Islamic era, and great scholars, before and after Tabarsi, have taken it into consideration. The number of Quranic homophones and similarities in some books published up to the ninth century have been fully studied statistically. However, Majmaulbayan of Tabarasi, which has dealt with them more comprehensively has not been given due attention. The present study investigated various cases of linguistic similarity in Majmaulbayan as well as the related lexical meanings. Similarity here does not mean homophones, where two or more different forms have the same pronunciation but different meanings. Rather, it means synonyms, where different words have similar meanings. In expressing similarities, Tabarsi used various terms such as âmotaqarebatulmaaniâ (having similar meanings), âalamaaniwahidâ(single meaning ), âmislâ(similar ), and âshabihâ( similar). When he wanted to refer to homophones, he mentioned homonymy without saying anything about similarities, while other scholars used homonyms together with other similarities in the sense of homophones. As for similarity in the sense of synonymy, Tabarsi did not believe in total synonymy, and he referred to lexical differences as âfarqâ or âforuqâ (differences). In this case, he followed Abuhalal Askari.